The crystal structures of α-Rb7Sb3Br16, α- And β-Tl7Bi3Br16 and their relationship to close packings of spheres - Chang, Jen-Hui; Doert, Thomas; Ruck, Michael (Zeitschrift fur Kristallographie - Crystalline Materials, 2020)
Yellow prismatic crystals of rubidium bromido-antimonate(III) Rb7Sb3Br16 and of two different modifications of thallium bromido-bismuthate(III) Tl7Bi3Br16 were obtained by solvent-free synthesis and by precipitation from acidic aqueous solutions. X-ray diffraction analyses revealed the Tl7Bi3I16-type for α-Tl7Bi3Br16 (orthorhombic, Cmcm, a = 2324.31(8) pm, b = 1346.69(4) pm, c = 3460.0(1) pm; Pearson symbol oC312) and a new structure type for β-Tl7Bi3Br16 (monoclinic, C2/c, a = 2331.87(5) pm, b = 1343.33(3) pm, c = 3546.01(7) pm, β = 102.708(1)°; mC312). The antimonate Rb7Sb3Br16 adopts the Tl7Bi3I16-type, too (orthorhombic, Cmcm, a = 2347.16(3) pm, b = 1357.89(5) pm, c = 3539.47(9) pm; oC312). The crystal structures of α- and β-Tl7Bi3Br16 comprise alternating slabs of isolated [BiBr6]3- octahedra and [Bi2Br10]4-octahedra pairs. Both structure types are hierarchically organized and can be regarded as sphere close packing with the same stacking sequence, if octahedra and octahedra pairs are replaced by spheres of equal size. The structural relationship between the Tl7Bi3I16-type and the hydrate Na7Bi3Br16 · 18H2O, which comprises similar structural features, is discussed.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Bromido-antimonate(III); Bromido-bismuthate(III); Close packing; Crystal structure; Halogenometalates